Shaping the future : the story of the Independent University of Bangladesh - Independent University of Bangladesh; Haq, Enamul; Independent University, Bangladesh (Dhaka : Independent University, Bangladesh, 1997)
An account of the Independent University, Bangladesh, a private university located in Dhaka.
Includes index.
Keywords: Independent University, Bangladesh -- History